The Emotional Experience of Mentally Disordered Offenders (MDO): An Exploratory Study Using Smallest Space Analysis (SSA). Issue 2 (15th March 2017) - Spruin, Elizabeth; Siesmaa, Belinda
ABSTRACT: The study explored the emotions felt during a criminal offense within a Mentally Disordered Offender (MDO) population and the impact that specific mental disorders have on an offender's emotional experience. Fifty-six MDOs were asked to complete a questionnaire that explored the emotions they felt during a specified offense. Using Smallest Space Analysis (SSA), results found two emotional regions within the population: Pleasure and Displeasure. Further analysis found that specific mental disorders have an impact on the emotional experience of offenders. Overall, the results highlighted that MDOs show differences in emotional functioning compared to offenders without mental disorders.